Kinerja Agen Di Atas Kapal Dalam Menangani Kedatangan Dan Keberangkatan Kapal Di PT. Putra Andalas Samudera Dumai - Habeahan, Hotmaida Rosari; Ginting, Dafid (Innovative: Journal Of Social Science Research, 2024)
One of the problems that often occurs is delays in ships docking and leaving the port, usually caused by agent delays in arranging the ship's arrival and departure. This research was conducted to determine the management of the arrival and departure of ships agented by PT. Putra Andalas Samudera Dumai and how to overcome these obstacles. The research methods used in this research are field research and library research methods, namely data obtained in the form of information about discussions both verbally and in writing. The findings from this research are: (1) The dock is full so ships have to wait in line to dock. (2) Network disruptions can cause all administrative activities on Inpornet to be paralyzed. (3) Lack of active pilots or pilots who do not carry out their duties properly in serving the ship docking process at the pier. Based on these findings, it is recommended to carry out the following efforts to overcome obstacles during the performance process of agents on board ships in handling the arrival and departure of ships at PT. Putra Andalas Samudera Dumai: (1) The arrangements are completed as quickly as possible by the shipping company handling the ship after knowing the Estimated Time Arrival (ETA) and Estimated Time Departure (ETD). (2) Adding facilities to support the loading and unloading process so that ships can be cleared according to the specified time. (3) HR that covers. (4) Scouts must have the awareness to carry out their duties and responsibilities and there must be sanctions for scouts who make mistakes in the process of carrying out their duties.